Economic growth in Cape Town : An assessment and redirection of Cape Town's Spatial Development Framework - Myers, Lauren (School of Architecture, Planning and Geomatics, 2014)
A challenge presented to city planners in Cape Town concerns the need to remedy spatial injustices and economic inequalities polarizing the city’s population. However, the current SDF does not sufficiently establish that the Voortrekker Road Corridor is the likely location for Cape Town's future economic backbone. This dissertation questions the feasibility of the Voortrekker Road Corridor project by testing the hypothesis that the city’s future economic backbone is unlikely to be situated along the West-East Voortrekker Road Corridor. This is accomplished by analysing growth trends in the non-residential property market. Evidence supporting the hypothesis was drawn using Geospatial Information System (GIS) analysis of the city’s recent spatial economic development using non-residential building area completions between 2005 and 2012. Informing these findings, interviews were conducted with property brokers, development managers and a senior urban planner at the City of Cape Town in order to gain expert insight into the property market in Cape Town. Rode’s Report analysing Cape Town’s property market for the first quarter of 2013 was also consulted, along with other reputable secondary sources. The results were and formed strong case for the nature of the city’s current spatial-economic trends. It was found that the most rapid rate of spatial economic growth is occurring along two north-south axes towards the northern peripheries. These development axes are broadly situated along N7 on the West Coast and along the R300’s northern segment towards Tygervalley and Brackenfell. What is more, spatial economic development is developing in several nodes, rather than along a single corridor. These have implications for planning to remedy spatial economic injustices in the city. It is argued that the SDF overestimates the capacity of planners to shape the course of spatial development, as is reflected by the encouragement of the East-West Voortrekker Road Corridor vision.